A Host Factor Involved in Hypovirus Symptom Expression in the Chestnut Blight Fungus, Cryphonectria parasitica - Faruk, M. Iqbal (American Society for Microbiology (ASM), 2008)
The prototype hypovirus CHV1-EP713 causes virulence attenuation and severe suppression of asexual sporulation and pigmentation in its host, the chestnut blight fungus, Cryphonectria parasitica. We identified a factor associated with symptom induction in C. parasitica using a transformation of C. parasitica strain EP155 with a full-length cDNA clone from a mild mutant virus strain, Cys(72). This was accomplished by using mutagenesis of the transformant fungal strain TCys(72)-1 by random integration of plasmid pHygR, conferring hygromycin resistance. The mutant, namA (after nami-gata, meaning wave shaped), showed an irregular fungal morphology with reduced conidiation and pigmentation while retaining similar levels of virulence and virus accumulation relative to TCys(72)-1- or Cys(72)-infected strain EP155. However, the colony morphology of virus-cured namA (VC-namA) was indistinguishable from those of EP155 and virus-cured TCys(72)-1 [VC-TCys(72)-1]. The phenotypic difference between VC-namA and VC-TCys(72)-1 was found only when these strains infected with the wild type or certain mutant CHV1-EP713 strains but not when infected with Mycoreovirus 1. Sequence analysis of inverse-PCR-amplified genomic DNA fragments and cDNA identified the insertion site of the mutagenic plasmid in exon 8 of the nam-1 gene. NAM-1, comprising 1,257 amino acids, shows sequence similarities to counterparts from other filamentous fungi and possesses the CorA domain that is conserved in a class of Mg(2+) transporters from prokaryotes and eukaryotes. Complementation assays using the wild-type and mutant alleles and targeted disruption of nam-1 showed that nam-1 with an extension of the pHygR-derived sequence contributed to the altered phenotype in the namA mutant. The molecular mechanism underlying virus-specific fungal symptom modulation in VC-namA is discussed.